Risiko Ekonomi pada Praktek Risywah dan Ihtikâr - Siti Kadariah; Tuti Anggraini; Marliyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
Ihtikâr in terminology is holding (hoarding) basic human goods to be able to gain profits by increasing the price and waiting for prices to soar in the market. According to the principles of Islamic law, whatever goods are permitted by Allah SWT to have them, then it is also lawful to be used as objects trading. Likewise, all forms that are forbidden to possess it are also forbidden to trade them. According to Yusuf al-Qardhawi, risywah is